Network Pharmacology and Experimental Validation to Reveal the Pharmacological Mechanisms of Liuwei Dihuang Decoction Against Intervertebral Disc Degeneration - Zhang H; Yao S; Zhang Z; Zhou C; Fu F; Bian Y; Luo H; Li Y; Yan S; Ge Y; Chen Y; Zhan K; et al. (Dove Medical Press, 2021)
Huihao Zhang,1,* Sai Yao,1,* Zhiguo Zhang,1,* Chengcong Zhou,1 Fangda Fu,1 Yishan Bian,1 Huan Luo,2 Yan Li,1 Shuxin Yan,1 Yuying Ge,1 Yuying Chen,3 Kunyu Zhan,4 Yanzhi Ge,1 Zuxiang Chen,1 Ming Yue,5 Xiaofeng Li,6 Weibin Du,1,7 Hongting Jin,1 Peijian Tong,1 Hongfeng Ruan,1,8 Chengliang Wu1 1Institute of Orthopaedics and Traumatology, The First Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China; 2Department of Pharmacy, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, People's Republic of China; 3The Fourth Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China; 4The Second Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China; 5Department of Physiology, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China; 6Department of Orthopedics and Traumatology, Shanghai Municipal Hospital of Traditional Chinese Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China; 7Research Institute of Orthopedics, The Affiliated JiangNan Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China; 8Longhua Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Hongfeng Ruan; Peijian TongInstitute of Orthopaedics and Traumatology, The First Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People's Republic of ChinaEmail rhf@zcmu.edu.cn; peijiantongzjtcm@163.comPurpose: To explore the pharmacological mechanisms of Liuwei Dihuang Decoction (LWDHD) against intervertebral disc (IVD) degeneration (IVDD) via network pharmacology analysis combined with experimental validation.Methods: First, active ingredients and related targets of LWDHD, as well as related genes of IVDD, were collected from public databases. The protein-protein interaction (PPI) network, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analyses were performed to predict the core targets and pathways of LWDHD against IVDD. Secondly, the IVDD model of mice treated with LWDHD was selected to validate the major targets predicted by network pharmacology.Results: By searching the intersection of the active ingredient targets and IVDD targets, a total of 110 targets matched the related targets of 30 active ingredients in LWDHD and IVDD were retrieved. PPI network analysis indicated that 17 targets, including Caspase-3, IL-1β, P53, etc., were hub targets. GO and KEGG enrichment analyses showed that the apoptosis pathway was enriched by multiple targets and served as the target for in vivo experimental study validation. The results of animal experiments revealed that LWDHD administration not only restored the decrease in disc height and abnormal degradation of matrix metabolism in IVDD mice but also reversed the high expression of Bax, Caspase-3, IL-1β, P53, and low expression of Bcl-2, thereby inhibiting the apoptosis of IVD tissue and ameliorating the progression of IVDD.Conclusion: Using a comprehensive network pharmacology approach, our findings predicted the active ingredients and potential targets of LWDHD intervention for IVDD, and some major target proteins involved in the predictive signaling pathway were validated experimentally, which gave us a new understanding of the pharmacological mechanism of LWDHD in treating IVDD at the comprehensive level.Keywords: intervertebral disc degeneration, Liuwei Dihuang decoction, network pharmacology, pharmacological mechanisms, apoptosis